Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1177/20539517231206804
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence and skills in the workplace: An integrative research agenda

Anoush Margaryan

Abstract: The development and diffusion of artificial intelligence (AI) technologies in workplaces are transforming the nature of work practices and their constituent skill requirements. This dual transformation is challenging for workers, organisations and societies, who are faced with the need to develop and enhance extant and new skills required to succeed in increasingly AI-mediated work settings. Although literature has recognised skills as a key factor in the development and uptake of AI technologies, there has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Students and teachers should develop a sense of justice, which governs them to converge on how to virtuously implement AI models in educational settings. It was shown that early exposure to technology concepts can significantly influence students' career paths and preparedness for the future (Bembridge et al, 2011;Margaryan, 2023). By introducing AI literacy at a young age, students develop a foundational understanding that paves the way for advanced learning and application in later stages of education and professional life.…”
Section: • Ai Ethicsmentioning
confidence: 99%
“…Students and teachers should develop a sense of justice, which governs them to converge on how to virtuously implement AI models in educational settings. It was shown that early exposure to technology concepts can significantly influence students' career paths and preparedness for the future (Bembridge et al, 2011;Margaryan, 2023). By introducing AI literacy at a young age, students develop a foundational understanding that paves the way for advanced learning and application in later stages of education and professional life.…”
Section: • Ai Ethicsmentioning
confidence: 99%